Dismantling the welfare state? Reagan, Thatcher, and the politics of retrenchment - Pierson, Paul 1959- (Cambridge University Press, 1994)
This book offers a careful examination of the politics of social policy in an era of austerity and conservative governance. Focusing on the administrations of Ronald Reagan and Margaret Thatcher, Pierson provides a compelling explanation for the welfare state's durability and for the few occasions where each government was able to achieve significant cutbacks. The programmes of the modern welfare state - the 'policy legacies' of previous governments - generally proved resistant to reform. Hemmed in by the political supports that have developed around mature social programmes, conservative opponents of the welfare state were successful only when they were able to divide the supporters of social programmes, compensate those negatively affected, or hide what they were doing from potential critics. The book will appeal to those interested in the politics of neo-conservatism as well as those concerned about the development of the modern welfare state. It will attract readers in the fields of comparative politics, public policy, and political economy
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1979-1993; Welfare state; Wohlfahrtsstaat; Sozialpolitik; Großbritannien; USA; United States / Social policy / 1980-1993; Great Britain / Social policy / 1979-